Extreme Events and Trends in the Indian Summer Monsoon - Krishnamurthy, V (Extreme Events and Natural Hazards: The Complexity Perspective, 2012)
This chapter contains sections titled: Introduction Data and Method of Analysis Low‐Pressure Systems Rainfall Surface Temperature Summary